The Influence of Education Level, Age, and Work Experience on Employee Work Productivity at the Kayangan District Office, Lombok Utara Regency - Yeni Dama Yanti; Akung Daeng; Adhitya Bagus Singandaru (Tinta Emas Publisher, 2024)
The aim of this research is to analyze the influence of education level, age and work experience on employee work productivity at the Kayangan District Office, Lombok Utara Regency. The population in this study were all employees at the Kayangan District Office, Lombok Utara Regency, totaling 38 people. Consisting of 22 civil servant employees and 16 non civil servant employees. The data collection method used in this research uses the census method. And the data collection technique used is through questionnaires and literature study. The analysis technique used uses a Likert scale and eviews 10, using multiple linear regression analysis methods, coefficient of determination test (R2), t test and simultaneous regression coefficient significance test (f test). The results of this research show that education level, age and work experience simultaneously influence employee work productivity at the Kayangan District Office, Lombok Utara Regency, the R2 value is 0.56, which means that the three independent variables used in the model are able to explain the independent variable by 56%, while The other 44% is influenced by other variables not examined in this study.